Apology Strategies in Scream Queens (2015) - Mariette Wahyuningsih Montgomery (Universitas Gadjah Mada, 2015)
The aim of this undergraduating thesis is to classify and identify apology strategies proposed by Cohen and Olshtain (1983) and its combinations in television series Scream Queens (2015), as a television series that illustrates how U.S. college students apologize. The data used in this research are utterances of Scream Queens (2015) season 1.The apologies found in the television series are classified based on the apology strategies proposed by Cohen and Olshtain (1983) which consist of: Expression of Apology (EA), Explanation of Account (Eac), Offer of Repair (OR), Acknowledgement Responsibility for Offense (ARO), and Promise of Forbearance (PF). Each apology speech act is classified based on the first strategy used. Utterances with two or more apology strategies are then identified and classified again according to the combinations. In this research, the total of apology strategies found thoughout their data source are 124. The most used apology strategy is EA with 59 utterances. There are 26 combinations and 4 standalone apology strategies in the television series. The most used combination is EA-EAc with 21 utterances. While the most used standalone apology strategy is EAc with 34 utterances.